TECHNOLOGICAL PROFICIENCY AND VIRTUAL COLLABORATION AS PREDICTORS OF GLOBAL ADAPTABILITY AMONG SOCIAL STUDIES PRE-SERVICE TEACHERS IN OYO STATE, NIGERIA - Ogundipe, Ololade Gbeminiyi; Oyewole, Oluwaseun (African Journal of Social and Behavioural Sciences, 2025)
This study investigated the roles of technological proficiency and virtual collaboration as predictors of global adaptability among social studies pre-service teachers in Oyo State, Nigeria. The sample comprised 153 pre-service teachers aged between 20 and 30 years, with a gender distribution of 60% female and 40% male. In an era of rapid technological advancement and global interconnectivity, the capacity for educators to adapt and thrive in diverse environments is crucial. Data were collected using three self-designed scales: the Technological Proficiency Scale (TPS), the Virtual Collaboration Scale (VCS), and the Global Adaptability Scale (GAS), which measure proficiency in technology, engagement in collaborative online activities, and adaptability to different cultural contexts, respectively. The findings revealed moderate levels of technological proficiency and engagement in virtual collaboration among participants. Statistically significant positive correlations were found between both technological proficiency (r = 0.482, p < 0.05) and virtual collaboration (r = 0.396, p < 0.05) with global adaptability. Furthermore, joint regression analysis indicated that technological proficiency and virtual collaboration explained 62% of the variance in global adaptability. In layman's terms, this means that pre-service teachers who are better at using technology and collaborating online are more likely to adjust successfully in diverse cultural settings. The study underscores the necessity for educational institutions to enhance training in technology and collaboration to better prepare future educators for the complexities of global citizenship and cultural adaptability. Recommendations include integrating more technology training and promoting collaborative projects within teacher education programs to improve these essential skills among future educators.